2022
DOI: 10.3389/fphar.2022.1095289
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure and the role of AhR in the tumor microenvironment of breast cancer

Abstract: Activation of the aryl hydrocarbon receptor (AhR) through environmental exposure to chemicals including polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzo-p-dioxins (PCDDs) can lead to severe adverse health effects and increase the risk of breast cancer. This review considers several mechanisms which link the tumor promoting effects of environmental pollutants with the AhR signaling pathway, contributing to the development and progression of breast cancer. We explore AhR’s function in shaping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 170 publications
0
16
0
Order By: Relevance
“…AhR plays a central role in cancer promotion pointing towards the non-genotoxic properties of PAHs. For instance, the AhR may directly regulate inflammatory responses and immune cells in the tumor microenvironment [ 113 ]. Moreover, nuclear AhR translocation, a hallmark of AhR activation, appears to be more common in female non-smokers with ADC, and it is associated with EGFR mutations [ 114 – 116 ].…”
Section: Lung Cancer Induced By Combustion Pm/pahsmentioning
confidence: 99%
See 1 more Smart Citation
“…AhR plays a central role in cancer promotion pointing towards the non-genotoxic properties of PAHs. For instance, the AhR may directly regulate inflammatory responses and immune cells in the tumor microenvironment [ 113 ]. Moreover, nuclear AhR translocation, a hallmark of AhR activation, appears to be more common in female non-smokers with ADC, and it is associated with EGFR mutations [ 114 – 116 ].…”
Section: Lung Cancer Induced By Combustion Pm/pahsmentioning
confidence: 99%
“…Consequently, the AhR may play a critical role in the TME of various cancer types by modulating the recruitment and function of infiltrating immune cells. Because AhR can be regulated by small molecules, the AhR has been suggested to be an attractive target for the tumor microenvironment and immunotherapy to treat cancer [ 113 , 364 , 365 ].…”
Section: Role Of Pahs and Ahr In Regulating The Tumor Microenvironmen...mentioning
confidence: 99%
“…It is also important to consider additional factors that may influence KP activity such as diet ( 67 ) and environmental contributors ( 181 , 182 ). Liang and colleagues demonstrated that nicotine-derived nitrosaminoketone (NNK) upregulates IDO1 via α7 nicotinic acetylcholine receptor (α7nAChR)-mediated activation of the factor c-Jun in lung tumors.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, individuals with non-small cell lung cancer who smoked had higher tumoral IDO1 levels and lower Trp/Kyn ratios compared patients who never smoked, further suggesting that smoking impacts KP activity ( 181 ). Exposure to other environmental toxicants can also activate AhR signaling ( 182 ), which may upregulate IDO expression resulting in immune suppression ( 48 ).…”
Section: Perspectivesmentioning
confidence: 99%
“… 6 8 Interestingly, the causal link between the action of these pollutants and certain cellular characteristics specific to metastases can also be established, involving the aryl hydrocarbon receptor, for example. 9 , 10 …”
mentioning
confidence: 99%